2006
DOI: 10.2320/matertrans.47.995
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness in an Extruded ZK60 Magnesium Alloy

Abstract: Examination of fracture toughness has been performed a commercial Mg-Zn-Zr alloy, ZK60, with fine strengthening particles. The commercial alloy was extruded at 633 K, and then heat treated at specific conditions. The microstructures were equi-axed grains, and average grain size and precipitate size were 11.6 mm and 50-150 nm, respectively. The yield strength and elongation-to-failure were 225 MPa and 17.0%. The plane-strain fracture toughness, K IC , was estimated to be 20.6 MPam 1=2 in stretched zone analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…4,6,[10][11][12]18) It is found that the present alloy has a good balance of strength and toughness, which shows a higher strength-toughness than that of conventional wrought magnesium and magnesium alloys. In general, the fracture toughness of magnesium is affected by the grain size.…”
Section: Comparison Of Fracture Toughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,[10][11][12]18) It is found that the present alloy has a good balance of strength and toughness, which shows a higher strength-toughness than that of conventional wrought magnesium and magnesium alloys. In general, the fracture toughness of magnesium is affected by the grain size.…”
Section: Comparison Of Fracture Toughnessmentioning
confidence: 99%
“…[13][14][15] In magnesium alloys, the existence of precipitates also influences the fracture toughness as in conventional alloys. [16][17][18] It has been reported that the spherical shaped precipitate is more effective for improving the fracture toughness than the rod shaped precipitates, 17) since they are more effective in the pinning of dislocations. On the other hand, a precipitate with a large diameter becomes easily the site of fracture, because of a creation of large strain field around these precipitates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20) On the other hand, in general, the particles have been known to affect the fracture toughness, because they become the void nucleation site due to the creation of a large strain field around them. The dispersion of a large size 21) and/or a high volume fraction of particles 22) are not effective, and the alloys containing these particles cause lower fracture toughness. Thus, understanding the role of the particles is important for improving the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…1) One of the effective ways for improving the ductility and fracture toughness of Mg alloys is grain refinement 2,3) because it promotes the prismatic hai slips, 4) and it facilitates the creation of a large plastic zone ahead of the fracture precrack. 5,6) In addition, the control of texture 7) and the control of size and distribution of precipitates 8) are effective for the enhanced ductility and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%